Dampak Struktur Organisasi terhadap Komitmen Organisasi: Perbandingan Antara Sektor Publik dan Swasta - Samhudi Samhudi; Basuki . Basuki; Rahmi Widyanti (Al-Kalam Jurnal Komunikasi, Manajemen dan Bisnis, 2024)
A good organizational structure will have an impact on employee organizational commitment. This study aims to examine the impact of organizational structure on organizational commitment in public and private sector companies in Banjarmasin. The three main structural dimensions included in this research are formalization, centralization (in the form of a hierarchy of authority and participation), and standardization. 100 questionnaires were distributed to 8 public and private companies in Banjarmasin and a sample of 80 valid questionnaires was obtained. The research results show that all structural dimensions have a relationship with organizational commitment in both sectors, except for authority hierarchy. Among the structural dimensions, formalization shows the greatest correlation with organizational commitment in public companies, while participation has the largest correlation with organizational commitment in private companies. Employee demographics have no impact on dimensions of organizational structure or commitment in either the private or public sectors. In addition, position in the private or public sector does not mediate the relationship between organizational structure and organizational commitment.